Applicable management dimensions during COVID-19: Case Montería -Colombia- - Ricardo-Jiménez, Luly Stephanie; Valencia-Burgos, Luis Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The COVID-19 generated great havoc in the economy, causing microentrepreneurs to overcome great challenges since the beginning of the pandemic. Thus, this article seeks to reflect on the managerial dimensions applicable by microentrepreneurs in the city of Montería during covid 19, through an investigation with a mixed approach of an exploratory nature, where a semi-structured interview was applied as an instrument where I deepen the problem with entrepreneurs, revealing as a result the skills that they consider essential for this type of challenge, based on the effect that covid 19 had on their companies.